DHAV-1 Blocks the Signaling Pathway Upstream of Type I Interferon by Inhibiting the Interferon Regulatory Factor 7 Protein - Lai, Yalan; Xia, Xiaoyan; Cheng, Anchun; Wang, Mingshu; Ou, Xumin; Mao, Sai; Sun, Di; Zhang, Shaqiu; Yang, Qiao; Wu, Ying; Zhu, Dekang; Jia, Renyong; et al. (Frontiers in Microbiology, 2021)
Duck hepatitis A virus (DHAV), which mainly infects 1- to 4-week-old ducklings, has a fatality rate of 95% and poses a huge economic threat to the duck industry. However, the mechanism by which DHAV-1 regulates the immune response of host cells is rarely reported. This study examined whether DHAV-1 contains a viral protein that can regulate the innate immunity of host cells and its specific regulatory mechanism, further exploring the mechanism by which DHAV-1 resists the host immune response. In the study, the dual-luciferase reporter gene system was used to screen the viral protein that regulates the host's innate immunity and the target of this viral protein. The results indicate that the DHAV-1 3C protein inhibits the pathway upstream of interferon (IFN)-β by targeting the IRF7 protein. In addition, we found that the 3C protein inhibits nuclear translocation of the IRF7 protein. Further experiments showed that the 3C protein interacts with the IRF7 protein through its N-terminus and that the 3C protein degrades the IRF7 protein in a caspase 3-dependent manner, thereby inhibiting the IFN-β-mediated antiviral response to promote the replication of DHAV-1. The results of this study are expected to serve as a reference for elucidating the mechanisms of DHAV-1 infection and pathogenicity.